Evaluation of the 75-second strength endurance test by comparing metabolic and biomechanical values in lab and field - Huber, A.; Goll, M.; Stöcker, F.; Spitzenpfeil, P.; Waibel, K. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Strength endurance is one of the key factors for a successful ski racing performance and of Alpine skiing`s strength and conditioning training. It is defined as fatigue resistance against repetitive load under static or dynamic muscle work. However, existing strength endurance testing settings come with a high strain on the athletes. The aim is finding a testing protocol that meets the quality criteria on objectivity, reliability, and validity and at the same time doesn`t expose the athlete to unnecessary strenuous testing procedures.